PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN KELOMPOK TANI “PATANI KOPI” DI DESA MEKARSARI KECAMATAN CIMAUNG KABUPATEN BANDUNG - Widiyaningrum, Widdy Yuspita; Latifah, Nur (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
Village governments play an important role in community development and empowerment. Villages are strategically positioned as the spearhead of government administration that is in direct contact with the community. This study uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The analysis refers to Soerjono Soekanto's role theory, which views the village government as a facilitator, educator, motivator, and catalyst, as well as Edi Suharto's empowerment theory, which is used to assess how villages raise awareness, capabilities, and independence in the community, and Deddy Mulyana's group theory, which emphasizes collective interaction in achieving common goals. The results of the study show: (1) as a facilitator, the village government provides seeds, fertilizers, training, and infrastructure, although in limited quantities; (2) as an educator, the village organizes coffee cultivation extension and training, but not yet on a regular basis; (3) as a motivator, the village fosters enthusiasm, collective awareness, and encourages youth involvement; and (4) as a catalyst, the village facilitates partnerships, opens up marketing access, and encourages product innovation. These roles have succeeded in increasing farmer capacity, production quality, and local economic independence, although there are still obstacles in terms of limited facilities, technology, and marketing networks.